2020
DOI: 10.1002/admi.201901952
|View full text |Cite
|
Sign up to set email alerts
|

Polysilazane‐Based Coatings with Anti‐Adherent Properties for Easy Release of Plastics and Composites from Metal Molds

Abstract: Polysilazanes are excellent coating materials, because of their self‐crosslinking in air at low temperatures, high chemical and thermal stability, elevated hardness, and excellent adhesion to many different substrates. Therefore, coatings of two chemically different polysilazanes (crosslinked Durazane 1800 (HTTS)/perhydropolysilazane (PHPS)) are deposited by either dip or spray coating and crosslinked at 200 or 300 °C in air to investigate the chemical composition, surface energy, and coating adhesion in depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…The development of antifouling coatings with hydrophobic character was also focused in recent years on “non-conventional” polymers. Barroso et al [ 65 ] investigated coatings based on pure polysilazane or loaded with poly(tetrafluoroethylene) (PTFE) particles. Such systems possess a higher amount of nonpolar organic groups resulting in a low surface free energy that was further lowered by the addition of PTFE fillers.…”
Section: Other Systemsmentioning
confidence: 99%
“…The development of antifouling coatings with hydrophobic character was also focused in recent years on “non-conventional” polymers. Barroso et al [ 65 ] investigated coatings based on pure polysilazane or loaded with poly(tetrafluoroethylene) (PTFE) particles. Such systems possess a higher amount of nonpolar organic groups resulting in a low surface free energy that was further lowered by the addition of PTFE fillers.…”
Section: Other Systemsmentioning
confidence: 99%
“…A similar tendency describing the change in contact angle with curing time for all coatings can be observed. Consider the D1500-rc coating as an example, the hydrophobic groups, such as, Si H 16 and Si CH 3 23 result in a hydrophobic surface with a contact angle of 94.6 ± 0.5 .…”
Section: Hydrophobicity Of Polysilazane Coatingsmentioning
confidence: 99%
“…The adhesion of polysilazane to most surfaces is known to be good due to the chemical reactions of Si H, Si NH groups with the OH groups and the adsorbed water molecules on surface, which form subsequently oxygen bridges between the polysilazane coating and the substrate. 16,39,40 Figure 9 shows the optical microscopy images of five polysilazane coatings cured after 1, 3, and 7 days and with the standard cross-cut tape test being performed. According to the DIN EN ISO 2409, coatings are classified from Gt 0 (best adhesion, without any detachment of the coating after the test) to Gt 5 (worst adhesion, detachment of the coating >65% of the tested area).…”
Section: Adhesion Of Polysilazane Coatings To Polycarbonate Substratementioning
confidence: 99%
See 1 more Smart Citation
“…They belong to the group of biomaterials used in prosthetic devices such as implant for breast enlargement, tissue augmentation and for treatment of hydrocephalus 49 . Although few experiments concerning the corrosion studies of polysilazane‐based surface coatings have indicated an excellent corrosion and oxidation resistance and more hydrophobicity, the in vitro performance of such coatings for biomedical applications are still far from being concluded 50,51 . Hoffmann and coworkers 52 studied two types of coatings, that is, sol–gel coatings (TiO 2 ) and precursor‐derived coatings in the system SiCN (Ti) on medical alloys (Ti6Al4V and Co28Cr6Mo alloy) for their biocompatibility and hindrance to toxic ions release from metal alloys.…”
Section: Surface Modification To Produce Biocompatible and Corrosion mentioning
confidence: 99%